Exploring Ayurvedic Solutions for Insomnia: Jatamansi Transdermal Patch as a Therapeutic Approach - Maksane, Sushant; Porwal, Palak (International Research Journal of Ayurveda & Yoga, 2025)
Insomnia is a widespread sleep disorder that significantly affects physical and mental well-being, leading to fatigue, cognitive dysfunction, and mood disturbances. Ayurveda offers a holistic approach to managing insomnia, focusing on natural remedies, herbal formulations, and lifestyle modifications, including Shodhana, Shirodhara, Nasya karma, and Murdhani Chikitsa. Among the various Ayurvedic treatments, Jatamansi (Nardostachys jatamansi) is highly regarded for its sedative, cooling, and restorative properties that help pacify vitiated Pitta and Vata doshas, which are often associated with sleep disturbances. In modern medicine, transdermal drug delivery systems have gained attention for their ability to provide controlled drug release through the skin. This paper explores the potential of a Jatamansi-based transdermal patch for treating insomnia, leveraging its calming and balancing effects on the body and mind. The preparation of the transdermal patch involves the use of key ingredients such as liners, adhesives, membranes, and backing, alongside a controlled drug release mechanism. The therapeutic potential of Jatamansi, with its multi-dimensional action on Rakta and Majja dhatus, is highlighted as an effective, natural remedy for improving sleep quality.